A generalization of the Lindelöf theorem - Zabolotskii, N. V.; Sheremeta, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We present a generalization of the Lindelöf theorem on conditions that should be imposed on the coefficients of the Taylor series of an entire transcendental function ƒ in order that the relation \(ln M_f (r) - τ r^ρ , r → ∞ , M_f (r) = \max \left\{ {\left| {f(r)} \right|:|z| = r} \right\}\) , be satisfied.